Cavitary Pneumonia Causes in the Arid Landscapes of Southern Arizona - Rawan El Kurdi; Krish H. Nayar; Michael B. Gotway; Janis Blair; Sandhya Nagarakanti (American Journal of Medicine Open)
Cavitary pneumonia, characterized by gas-filled spaces within lung tissue, is commonly associated with bacterial pathogens, such as Staphylococcus aureus, Streptococcus, Pseudomonas, and Klebsiella species. This study aimed to investigate the most common causes of cavitary pneumonia in southern Arizona, where coccidioidomycosis is endemic. Fungal infections were the predominant cause of cavitary pneumonia (69%), either alone or in association with bacterial infections. Seven percent of patients had concurrent fungal and bacterial infections. Overall, coccidioidomycosis was the most common cause of cavitary pneumonia, accounting for 39% of all cases and 82% of fungal cases. Among these, 24% had proven coccidioidomycosis, 51% had probable infections, and 25% had possible infections. Bacterial infections accounted for 30% of cavitary pneumonia cases, with Staphylococcus aureus (12%), Streptococcus species (12%), and Pseudomonas species (11%) being the most prevalent organisms. Overall mortality was 25%, with 34% of deaths directly attributed to cavitary pneumonia.